Growing Gardening Metaphors the Activity in Teaching Writing Recount Text for First Grade of Senior High School - Yahya Sidiq; Aryuliva Adnan (Journal of English Language Teaching, 2019)
Abstract This paper deals with the use of Growing Gardening Metaphors Classroom Activity in teaching writing recount text for first grade of senior high school. Growing Gardening Metaphors can be used by teachers to make teaching and learning English classroom more enjoyable. This metaphor activity is used as the solution for the teacher to solve students’ problem in writing recount text in the first grade of senior high school. It helps the teacher in teaching writing recount text which motivates students to think more creative in considering the same function or activity both their experience and garden vocabulary while writing the text. Growing Gardening Metaphor can be applied for senior high school students in Indonesia.  For doing this classroom activity, the teacher needs approximately 60 minutes to take the time required. It is appropriate to the grade X in senior high school which has two “teaching and learning hours” a week or 90 minutes for learning the English language based on the Indonesia Curriculum of 2013.Keywords: Teaching writing, recount text, Growing Gardening Metaphors.